The outcome of interprofessional education: Integrating communication studies into a standardized patient experience for advanced practice nursing students. Issue 1 (January 2016) - Defenbaugh, Nicole; Chikotas, Noreen E.
Abstract: The purpose of this qualitative study was to examine the impact of standardized patient experiences (SPE) in the education of the Advanced Practice Nurse (APN). The education of the APN requires educators to make every attempt to promote competency in the areas of communication and clinical-decision making. SPE programs have been found to improve the interpersonal, problem solving, and critical thinking skills of nursing students. For this research twenty-nine APN students participated in SPEs over the course of two semesters. Fifteen student volunteers of those 29 participants were then interviewed three months after the experience. Results revealed that having an expert in the field of communication studies increased awareness of communication skills and how to improve nurse-patient encounters in the clinical setting. The interprofessional collaboration during the SPEs assisted in facilitating the application of learned communication skills into patient-centered care of the APN student.